2022
DOI: 10.1007/s42235-022-00251-8
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Collagen/Sodium Alginate Hydrogels for Bioprinting of Skin Models

Abstract: 3D printing technology has great potential for the reconstruction of human skin. However, the reconstructed skin has some differences from natural skin, largely because the hydrogel used does not have the appropriate biological and physical properties to allow healing and regeneration. This study examines the swelling, degradability, microstructure and biological properties of Collagen/Sodium Alginate (Col/SA) hydrogels of differing compositions for the purposes of skin printing. Increasing the content of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Higher MD of human CMA compared to bovine CMA may allow for more robust cross-linking of the printed construct and thereby yield constructs with better print fidelity. On the basis of the 3D printing results of this study, bovine- and human-derived collagen can be used as bioinks for extrusion-based printing of collagenous constructs for use in ACL reconstruction and skin regeneration applications. , 3D printing of architecturally complex tissues can be feasible by designing stereolithography (STL) models, and the layer-by-layer fidelity in the microarchitecture of the resultant prints can be quantified using techniques such as SEM and micro-CT. Additionally, extrusion-based printing is dependent on the ink’s specific shear thinning coefficients which aid in ease of ink ejection and the formation of prints with high structural fidelity following deposition. , It is likely that the shear-thinning properties of rat collagen may not be conducive to extrusion-based 3D printing, and therefore use of microvalve or inkjet printing methods may be more suitable for the formation of viable rat collagen constructs for tissue engineering applications. ,,, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher MD of human CMA compared to bovine CMA may allow for more robust cross-linking of the printed construct and thereby yield constructs with better print fidelity. On the basis of the 3D printing results of this study, bovine- and human-derived collagen can be used as bioinks for extrusion-based printing of collagenous constructs for use in ACL reconstruction and skin regeneration applications. , 3D printing of architecturally complex tissues can be feasible by designing stereolithography (STL) models, and the layer-by-layer fidelity in the microarchitecture of the resultant prints can be quantified using techniques such as SEM and micro-CT. Additionally, extrusion-based printing is dependent on the ink’s specific shear thinning coefficients which aid in ease of ink ejection and the formation of prints with high structural fidelity following deposition. , It is likely that the shear-thinning properties of rat collagen may not be conducive to extrusion-based 3D printing, and therefore use of microvalve or inkjet printing methods may be more suitable for the formation of viable rat collagen constructs for tissue engineering applications. ,,, …”
Section: Discussionmentioning
confidence: 99%
“…54,55 It is likely that the shear-thinning properties of rat collagen may not be conducive to extrusion-based 3D printing, and therefore use of microvalve or inkjet printing methods may be more suitable for the formation of viable rat collagen constructs for tissue engineering applications. 49,50,55,56…”
Section: Discussionmentioning
confidence: 99%
“…In 3D printing, collagen mixed with materials is rather popular. To achieve the best printable rows, collagen and sodium alginate can be blended to obtain hydrogels with excellent mechanical and biological properties [ 99 ]. Tian et al found that a 1% collagen composite hydrogel was shown to be a suitable bio-ink for the biofabrication of a bilayer skin construct.…”
Section: Three-dimension Hydrogelsmentioning
confidence: 99%
“…Tian et al found that a 1% collagen composite hydrogel was shown to be a suitable bio-ink for the biofabrication of a bilayer skin construct. Fibroblasts and keratinocytes spread and proliferate in the bilayer skin [ 99 ]. In the study of Niu et al, sodium alginate/gelatin/collagen (SA/Gel/C) hydrogel as a bio-ink was used to construct a bionic full-thickness skin scaffold [ 100 ].…”
Section: Three-dimension Hydrogelsmentioning
confidence: 99%
“…The technique allows computerbased production of multilayer 3D constructs with versatile structural and biological attributes [24]. The commonly used extrusion-based 3D printing modality depends on inks often made of bioactive polysaccharide polymers such as hyaluronic acid (HA), sodium alginate and chitosan (CS) as well as peptides and proteins [25][26][27]. As a nanofibrous (NF) component would endow the 3D printed scaffold with physical nanopores alongside the space available between adjacent cross-links in the hydrogel polymer network, inclusion of electrospun NF may promote cell anchoring and regenerative healing.…”
Section: Introductionmentioning
confidence: 99%